3D anisotropic full-waveform inversion for complex salt provinces - Li, Junxiao; Rusmanugroho, Herurisa; Kalita, Mahesh; Xin, Kefeng; Dzulkefli, Farah Syazana (Frontiers in Earth Science, 2023)
Seismic imaging and inversion become extremely challenging when dealing with salt structures. Conventional state-of-the-art full-waveform inversion (FWI) fails to recover those features in areas where salt is present. A widely used solution in industry, however, involves substantial human-interpretation. In this study, a regularized isotropic FWI that penalizes the velocity drops in depth is introduced to recover the top parts of salt bodies. Then an automatic salt flooding is applied to reconstruct deeper parts of the salt. Finally, in order to improve the accuracy of inverted model, which is strongly affected by anisotropy, an anisotropic FWI is used to update velocity model. We tested the approach on both synthetic and field datasets. Our FWI results have revealed satisfying salt recovery as well as detailed velocity features in areas close to salt bodies.